(3GdeLjO aj EYQGH GdbQBf GdeLjOs - (3GdSaGbSj , EHQGgje Hf eMeO Hf EHQGgje GdbjSj, HQgGf GdOjf CHh ESMGb,J (B742 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3jHOC HGYQGH ShQI Wg Hbhdg (B: (3Wg GdXGgQ CfgG ef GdMQha GdebWYI hbO JbOe GdcdGe YdjgG ai Chd GdHbQI s
(3BNQgG (B:s
(3ai GYQGH ShQI GdfGS bhdg hGeG GdfGS GdCNjQ abjd eYWha Ydi Pi GdhShGS Ci ef TQ GdbHdjf hbjd eYWha Ydi GdLfI , hGddg CYde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B82s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs